PD-L1-Mediated Immunosuppression in Glioblastoma Is Associated With the Infiltration and M2-Polarization of Tumor-Associated Macrophages - Zhu, Zhiyuan; Zhang, Hongbo; Chen, Baodong; Liu, Xing; Zhang, Shizhong; Zong, Zhitao; Gao, Mengqi (Frontiers in Immunology, 2020)
Immune checkpoint inhibitors have so far yet achieved substantial progress in glioblastoma. PD-1/PD-L1 axis predominantly contributes to the immunosuppressive tumour microenvironment, in which tumour-associated macrophages (TAMs) are critical mediators. This study aims to investigate the potential role of PD-L1 in regulating TAMs in glioblastoma. Gene expression data and clinical information of glioma patients were collected from TCGA (n=614) and CGGA (n=325) databases. Differentially expressed genes between PD-L1high and PD-L1low groups were identified and subjected to bioinformatical analysis. We found that PD-L1 was frequently expressed in gliomas with a grade-dependent pattern. Higher PD-L1 expression predicted shorter overall survival. Moreover, PD-L1 was positively correlated with immunosuppressive cells (macrophage, neutrophil, immature DC) and negatively correlated with cytocidal immune cells (CD8+ T cell, Th1). Importantly, PD-L1 high expression was significantly correlated with M2-polarization of macrophages (M2-TAMs). We conclude that PD-L1 is an unfavourable prognostic marker for patients with glioblastoma; PD-L1-mediated immunosuppression may attribute to the infiltration and M2-polarization of TAMs.